Znaczenie kultury w wychowaniu chrześcijańskim - Helena Słotwińska (Nicolaus Copernicus University in Toruń, 2011)
The article touches upon five issues. Its opening section expounds in detail on multifarious aspects of the notion of culture. In the following sections culture is shown as a vehicle by means of which the world and culture itself can be perfected. Moreover, the article depicts the relationship between God's message of salvation, on the one hand, and culture, on the other. The final section explores links involving Christian education and culture. The article indicates that having been called into existence man was also called to become a creator of culture. Men and women pursue this calling through perfecting themselves and the world around. While realizing the fact that love is the essence of perfection, a Christian ought to perceive his life in terms of growth in the spirit of love towards God, people and the world.